Randomised controlled trial of topical ciclosporin A in steroid dependent allergic conjunctivitis - Daniell, M (BMJ Group, 2006)
AIM: To evaluate the efficacy, safety, and therapeutic effect of topical ciclosporin A 0.05% as a steroid sparing agent in steroid dependent allergic conjunctivitis. METHODS: Prospective, randomised, double masked, placebo controlled trial comparing signs, symptoms, and the ability to reduce or stop concurrent steroid in steroid dependent atopic keratoconjunctivitis and vernal keratoconjunctivitis using 0.05% topical ciclosporin A compared to placebo. Steroid drop usage per week (drug score), symptoms, and clinical signs scores were the main outcome measures. RESULTS: The study included an enrolment of 40 patients, 18 with atopic keratoconjunctivitis and 22 with vernal keratoconjunctivitis. There was no statistical significant difference in drug score, symptoms, or clinical signs scores between the placebo and ciclosporin group at the end of the treatment period. No adverse reactions to any of the study formulations were encountered. CONCLUSIONS: Topical ciclosporin A 0.05% was not shown to be of any benefit over placebo as a steroid sparing agent in steroid dependent allergic eye disease.